2007
DOI: 10.2337/dc07-0140
|View full text |Cite
|
Sign up to set email alerts
|

Normoalbuminuric Renal-Insufficient Diabetic Patients

Abstract: OBJECTIVE -About 20% of diabetic patients with chronic kidney disease (CKD) detected from the new American Diabetes Association recommendations (albumin excretion rate Ͼ30 mg/24 h or estimated glomerular filtration rate [GFR] Ͻ60 ml/min per 1.73 m 2 ) may be normoalbuminuric. Do the characteristics and outcome differ for subjects with and without albuminuria?RESEARCH DESIGN AND METHODS -A total of 89 patients with diabetes and a modification of diet in renal disease (MDRD) estimated GFR (e-GFR) Ͻ60 ml/min per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
86
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 36 publications
19
86
2
1
Order By: Relevance
“…In this aspect, Yokoyama et al [17] described that the proportion of subjects with low eGFR (\60 ml/min per 1.73 m 2 ) and normoalbuminuria was 11.4 % of type 2 diabetic patients examined (262/2,298). Supporting our notion, Rigalleau et al [18] reported that risk for renal progression in such patients with type 1 or type 2 diabetes is lower. On the contrary, allcause mortality, not cardiovascular events, was strongly associated with reduced eGFR \30 ml/min per 1.73 m 2 in normoalbuminuric diabetic patients in this present study.…”
Section: \0001supporting
confidence: 78%
“…In this aspect, Yokoyama et al [17] described that the proportion of subjects with low eGFR (\60 ml/min per 1.73 m 2 ) and normoalbuminuria was 11.4 % of type 2 diabetic patients examined (262/2,298). Supporting our notion, Rigalleau et al [18] reported that risk for renal progression in such patients with type 1 or type 2 diabetes is lower. On the contrary, allcause mortality, not cardiovascular events, was strongly associated with reduced eGFR \30 ml/min per 1.73 m 2 in normoalbuminuric diabetic patients in this present study.…”
Section: \0001supporting
confidence: 78%
“…Albuminuria was found only in 30% of patients with RI at baseline, in line with previous studies in which the majority of patients with type 2 diabetes and RI were found to be normoalbuminuric [40][41][42]. Both albuminuria and RI are independent risk factors for CVEs and all-cause mortality in type 2 diabetes, with albuminuria being the strongest risk factor and relevant at all levels of renal function.…”
Section: Discussionsupporting
confidence: 89%
“…A previous report from the UK (2) revealed that 30% of diabetic patients had CKD stage 3, which was similar to our result indicating a higher prevalence of CKD in diabetic patients than the general population. Our survey also demonstrated that 64% of diabetic patients with CKD stage 3 were normoalbuminuric, in contrast to the results which showed that normoalbuminuric patients were about 20 to 30% in CKD stage 3 patients (11,12). ACEIs and ARBs might have modified both ACR and eGFR, although the absolute number of patients on these drugs in our study were fewer than in the previous studies (11,12 (11,12 …”
Section: Discussioncontrasting
confidence: 78%